C-Lando: Literacy innovation of digital-based Indonesian cultural maps as an effort to increase exploration of the archipelago's heritage / Muhamad Catur Gunawan ... [et al.] - Gunawan, Muhamad Catur; Drajad, Rizma; Apriyanti, Siti; Alinda H, Refina (2024)
Indonesia, as an archipelago of more than 17.000 islands, has a diverse range of cultural traditions, languages, and historical relics. However, this cultural wealth is still not widely known by local communities and international visitors. The strengthening context of globalization also makes Indonesian culture face the challenge of remaining relevant and preserved in a society that tends to be more interested in foreign cultures. In Indonesia, this phenomenon is even more pervasive with the rapid flow of information and the influence of foreign cultures through social media and digital platforms. This paper underscores the importance of coming up with innovative solutions to strengthen Indonesia's cultural identity. The utilization of digital technology in this initiative allows users to access detailed information on historical sites, traditional arts and crafts, local festivals, and indigenous communities across the archipelago. The platform aims to preserve and introduce Indonesia's rich culture to current and future generations. As the Indonesian culture is faced with internal challenges in maintaining public interest in local cultural heritage, C-Lando comes as the right answer to overcome this. C-Lando is a platform that combines digital technology with Indonesian cultural values, providing easy and interesting access for users to explore and understand more about Indonesia's cultural diversity. Through this platform, it is hoped that a deeper understanding of the uniqueness and beauty of Indonesian culture can be created, as well as strengthening the love of the country in the midst of increasingly strong globalization.